Developmental emergence of first- and higher-order thalamic neuron molecular identities - Lo Giudice, Quentin; Wagener, Jan Robin; Abe, Philipp; Frangeul, Laura; Jabaudon, Denis (Development, 2024)
The thalamus is organized into nuclei that have distinct input and output connectivities with the cortex. Whereas first-order (FO) nuclei - also called core nuclei - relay input from sensory organs on the body surface and project to primary cortical sensory areas, higher-order (HO) nuclei - matrix nuclei - instead receive their driver input from the cortex and project to secondary and associative areas within cortico-thalamo-cortical loops. Input-dependent processes have been shown to play a crucial role in the emergence of FO thalamic neuron identity from a ground-state HO neuron identity, yet how this identity emerges during development remains unknown. Here, using single-cell RNA sequencing of the developing mouse embryonic thalamus, we show that, although they are born together, HO neurons start differentiating earlier than FO neurons. Within the FO visual thalamus, postnatal peripheral input is crucial for the maturation of excitatory, but not inhibitory, neurons. Our findings reveal different differentiation tempos and input sensitivities of HO and FO neurons, and highlight neuron type-specific molecular differentiation programs in the developing thalamus.